Aflatoxin B1 occurrence in millet, sorghum and maize from four agro-ecological zones in Kenya - Sirma, A.J.; Senerwa, D.M.; Grace, Delia; Makita, K.; Mtimet, Nadhem; Kang'ethe, Erastus K.; Lindahl, Johanna F. (African Journal of Food, Agriculture, Nutrition and Development, 2016)
Aflatoxin-contaminated food is a public health concern. Contamination of staple foods in Kenya has in the past led to loss of human lives as well as condemnation of large quantities of food, contributing to food insecurity. This study investigated the occurrence of aflatoxins in maize, millet and sorghum from five counties in Kenya (Kwale, Isiolo, Tharaka-Nithi, Kisii and Bungoma) representing four agro-ecological zones (AEZs). Samples were collected from rural households in two phases between February and October 2014. Using competitive enzyme-linked immunosorbent assay (ELISA), 497 maize, 205 millet and 164 sorghum samples were screened for the presence of aflatoxin B1. Overall, 76% of maize, 64% of millet and 60% of sorghum samples were positive for aflatoxin B1. Of these, the proportion of samples with aflatoxin B1 levels above the Kenya Bureau of Standards limit of five parts per billion was 26% for maize, 10% for millet and 11% for sorghum. In samples collected during the second phase, there were significant differences in the mean levels of aflatoxin contamination between the agroecological zones (p<0.05); maize from Kisii and Bungoma, representing temperate AEZ, had the lowest mean contamination, whereas millet and sorghum from Tharaka-Nithi (humid) and Isiolo (semi-arid), respectively, had the highest mean contamination. Continued exposure to aflatoxins via food in Kenya poses a threat to human health.